The relationship between negative emotions and adjustment disorder in young adults: the mediating role of rumination and insomnia - Shao, Xinyue; Dong, Zhao; Zhang, Shuai; Qiao, Yunyun; Zhang, Hongwei; Guo, Hua (Frontiers in Psychiatry, 2025)
IntroductionThis study aimed to investigate the influence of negative emotions on adjustment disorder (AjD) in young adults, focusing on the mediating role of rumination and insomnia.MethodsThe study recruited 2015 young patients (aged 18–35) receiving treatment at the Psychosomatic Medicine Department of the Affiliated Encephalopathy Hospital of Zhengzhou University from February 2023 to March 2024. Participants completed the Depression Anxiety and Stress Scale (DASS), Ruminative Responses Scale (RRS), Insomnia Severity Scale (ISI), and Adjustment Disorder – New Module 20(ADNM-20) to assess negative emotions, rumination thinking, sleep status, and AjD. Data were analyzed utilizing descriptive statistics, correlation, hierarchical linear regression, and mediation analyses.Results1) AjD was significantly influenced by being an only child and family composition, but there was no significant gender difference. Scores for negative emotions, rumination, insomnia, and AjD varied significantly different among different age groups, with the 30–35 age group scoring significantly higher than others. 2) Total scores for the DASS-21and its subscales, the RRS and its subscales, insomnia, and AjD were significantly correlated (p < 0.01). Negative emotions and ruminative thoughts predicted AjD, accounting for 47.8% of the total variation in AjD. 3) Negative emotions positively predicted AjD (β = 0.37, p < 0.001). Negative emotions affect AjD in young adults through rumination and insomnia alone and together, and the mediating effect accounts for 34%, 7.9%, and 20% of the total effect.DiscussionThe study’s findings suggest that rumination and insomnia play significant mediating roles in the relationship between negative emotions and AjD in young adults. Negative emotions directly affect AjD and have indirect effects through rumination and insomnia.